2004
DOI: 10.1266/ggs.79.331
|View full text |Cite
|
Sign up to set email alerts
|

Nonconcerted evolution of histone 3 genes in a liverwort, Conocephalum conicum

Abstract: To estimate the extent of genetic variation at the DNA level, the histone 3 (H3) genes were sequenced from single individual each from the three cryptic species recognized based on allozyme analyses, YFS, J and T types of Conocephalum conicum and two closely related species, C. japonicum and Marchantia polymorpha . Although the H3 genes are known to be highly conserved, the nucleotide diversities were 0.128, 0.109, 0.108, 0.049 and 0.034. These values are 30 to 100 times higher than that in Drosophila melanoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Excluded from analysis were known and suspected centromeric histone H3 sequences (Baker and Rogers 2006;Dalal et al 2007;Talbert et al 2004), pseudo genes, tissue-specific H3 variants such as histone H3t, found in human testes (Tachiwana et al 2008), and sequence records with high apparent error rates that precluded identification of established histone H3 features (Luger et al 1997). Histone sequences, deposited as plant histones (Kim and Yamazaki 2004) but obviously arising from fungal or insect contaminants, were identified ( Fig. S2A) 2 and excluded from TOL analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Excluded from analysis were known and suspected centromeric histone H3 sequences (Baker and Rogers 2006;Dalal et al 2007;Talbert et al 2004), pseudo genes, tissue-specific H3 variants such as histone H3t, found in human testes (Tachiwana et al 2008), and sequence records with high apparent error rates that precluded identification of established histone H3 features (Luger et al 1997). Histone sequences, deposited as plant histones (Kim and Yamazaki 2004) but obviously arising from fungal or insect contaminants, were identified ( Fig. S2A) 2 and excluded from TOL analyses.…”
Section: Methodsmentioning
confidence: 99%